Telecommunications infrastructures and policies as factors in regional competitive advantage and disadvantage - David Newlands; Melanie Ward (European Regional Science Association (ERSA), 1998)
There has been a revolution in telecommunications technologies in recent years. New technologies with myriad applications have helped transform markets, industrial structures and the organisation of firms throughout the economy. These changes have had important spatial effects which are the subject of this paper. The processes of adoption and diffusion of telecommunications technologies are discussed. The argument that the spread of such technologies means that"distance no longer matters" is scrutinised. There is a theme in the literature that this decentralising tendency has particular implications for peripheral regions, that new communications technologies could have a significant impact in reducing the traditional economic disadvantages of such regions. However, there is a contrary argument that there remain strong centralising tendencies. Indeed, new communications technologies may be associated with an increasing polarisation of economic activity. These theoretical arguments are revisited in the context of a case study of the Scottish Highlands and Islands. This is a particularly interesting region because, although it is a peripheral, rural area, it has a highly developed telecommunications infrastructure. This case study deploys the results of a recent study of the use by firms in the Highlands and Islands of communications technologies. The paper finds little significant evidence that telecommunications initiatives in the Scottish Highlands and Islands have significantly altered the competitive position of the region. The paper concludes with a discussion of some of the implications for national and local policy makers in encouraging the take up and effective use of new communications technologies.
Keywords: 330